Development of Section Comb Media as a Project Tool in Learning Hair Coloring - Sukesi, Siti; Ihsani, Ade Novi Nurul; Qudus, Nur; Supraptono, Eko (Universitas Negeri Semarang, 2025)
This research was motivated by the suboptimal achievement of hair coloring learning competencies. To address student difficulties in learning hair coloring, it is necessary to develop learning media relevant to student needs, namely section combs. This research aims to: develop section combs as teaching aids in hair coloring learning; determine the feasibility of section combs as teaching aids in hair coloring learning; determine the effectiveness of section combs in improving students' hair coloring skills; and determine the practicality of section combs. This research uses the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data analysis used in this study consisted of: quantitative descriptive analysis to determine the feasibility of section combs; N-Gain and independent sample t-tests to determine the effectiveness of section combs; and percentage distribution analysis to determine practicality. The feasibility test results found that the section combs were categorized as very feasible. The results of the effectiveness test found an N-Gain value of 58.47, included in the fairly effective category, and a T-Test value of 24.787, there was a significant increase between the average N-Gain of the experimental class and the control class. The practicality test of the section comb teaching aid found a value of 84, included in the